Learning Lessons, Challenges, Impacts & Solutions on the Path of Recovery from Covid-19 in Nepal - Rana, Poonam R L (Nepalese Culture, 2021)
The research study focuses on the impact of Covid-19 on Tourism in Nepal and looks into the challenges to face in the path of recovery and to bring to light the lessons learned from COVID 19. It is qualitative in nature including both primary and secondary sources. 50 respondents were chosen as samples. The results showed that, there was drastic impact on tourism sector affecting national economy, It has brought to light various challenges to be faced in path of recovery and the greatest lesson learnt is that the government should develop its health sector and the people should always be strong and prepared to face any disaster or pandemics at all times. Solutions are provided in form of recommendations.